Trend Topic Analysis for Wind Energy Researches: A Data Mining Approach Using Text Mining - Eroglu, Yunus; U. Seçkiner, Serap (Journal of Technology Innovations in Renewable Energy, 2016)
This study reviews and analyses the recent research and development and trends in the applications of wind energy and it also discusses and summarizes the topic. We show the usage and the influence of text mining on the different aspects of wind energy systems especially for hot topics and trends of wind energy area. Text mining provides the state of the art in this area that will be a good guidance for future research work. The main results achieved from the study have shown that the text mining technique are adequate for serving as a proof of concept and as a test-bed for deriving requirements for the development of more generally applicable text mining tools and services within wind energy science.